PENDIDIKAN ISLAM DALAM PERADABAN INDUSTRI FASHION - Mustami, Ahmad (Hunafa: Jurnal Studia Islamika, 2015)
This article discusses the concept Apparel in Islamic education . Which is currently a lot of variety of fashion in dress. Although the general function of clothes is a human genitalia cover and protect the body from the heat of the sun. However hijab at this time not just cover the nakedness , but rather as a fashion style that became a common thing now is infecting the womenfolk including Muslim. Ranging from clothes, pants, until hijab began in innovation so as to attract the eye. Although it is not yet represent the shape and fashion model/standard clothes, but felt able to express Islamic education in the dressing (hijab) and a fashion model/Islamic clothing. Obviously keep on religious norms, ethical and moral teachings. Substance of clothing in Islam is polite in accordance with the values of Islamic Education.